Boosting the efficiency of narrowband THz radiators via three-dimensional emission collection - Tinglian Zhang; Rasmus Ischebeck; Uwe Niedermayer; Thomas Schietinger; Pavle Juranić (Physical Review Accelerators and Beams)
The demand for high-power, narrowband, and tunable THz radiation sources is steadily increasing. Smith-Purcell radiation offers a compact method for resonantly generating narrowband THz sources with notable advantages over other approaches, though the power output still requires improvement. This work introduces a novel 3D emission-collection concept that enhances the efficiency of THz radiators, achieving an enhancement of over an order of magnitude in coherent radiation power compared to the 2D approach. Systematic simulations reveal that the single-layer helically rotated structure, optimized through inverse design, emits stronger THz radiation than other reported circumferentially closed gratings, achieving millijoule radiated energy. Helix gratings exhibit significant potential for developing accelerator-based high-power and tunable THz radiators and are easy to manufacture. Some methods concerning optimizing beam-grating properties are employed to improve the radiated THz intensity. These results provide new insights into developing high-power THz radiators, which may provide an alternative THz source for free-electron laser facilities.